ASOSIASI KEBIASAAN MEROKOK DENGAN KEJADIAN DEMENSIA PADA LANSIA: STUDI CROSS-SECTIONAL - Alvin Abdillah; Agus Priyanto; Luluk Fauziyah Januarti (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: The elderly refer to individuals who have entered the final phase of the aging process. life phase. As age increases, not only does our body experience a decline in function, but our brain does too, which causes many elderly people to become forgetful. Forgetfulness (declining cognitive function) is often referred to as dementia. Aim: The aim of this research is to analyze the relationship between smoking habits and the incidence of dementia in the elderly at the Posyandu in Duko Tambin Village under the Tragah Health Center. Method: This study uses a correlational analytic approach with a cross-sectional design. The research was conducted at the Posyandu in Duko Tambin Village, Bangkalan Regency. The elderly population in Duko Tambin Village consists of 125 people. The sample size is 96 people. Subjects were selected using purposive sampling. The independent variable is smoking habits, while the dependent variable is the incidence of dementia. The research instrument includes a smoking habits questionnaire and the MMSE. Data analysis was performed using the Spearman rank test. Results: The results of the analysis of elderly data at the Posyandu in Duko Tambin Village regarding smoking habits show that almost all belong to the heavy category at 80%, and most of the elderly are in the severe dementia category at 70%. The Spearman rank statistical test yielded a p-value of 0.044, meaning there is a relationship between smoking habits and the incidence of dementia in the Posyandu of Duko Tambin Village, which is the working area of the Tragah Public Health Center. Conclusion: Based on the results above, it is recommended that the elderly reduce or quit smoking as it can lead to dementia. This is due to the nicotine present in cigarettes, which can cause dementia